Barriers and facilitators to scale-up of hospital-at-home: an observational cohort study protocol - Ko, Stephanie Q.; Low, Shi Yun; Sevdalis, Nick (Frontiers in Health Services, 2025)
IntroductionHospital-at-Home interventions have been shown to be clinically and cost-effective, and many healthcare systems internationally are investing in scaling-up such interventions. However, most existing studies focus on how effective the intervention is, rather than how to successfully scale it up. We report a study protocol for a theory-driven investigation of a Hospital-at-Home intervention. We propose a novel combination of two established implementation science frameworks—the EPIS framework and the Scale-Up framework—and apply it to a planned scale-up of a Hospital-at-Home intervention in Singapore.Methodsand analysis: This will be an observational cohort study across 23 months (May 2022 to April 2024) to evaluate the association of outer and inner contextual factors on key implementation outcomes—the volume of patients admitted, operational efficiency and levels of adoption. Statistical process control graphs will be used to examine variation in the implementation outcomes over time. Linear regression will be applied to assess associations of outcomes with contextual factors that are continuous variables; logistic regression will be applied to assess the associations of outcomes with binary/descriptive contextual factors. To supplement these, qualitative methods will be applied using a content analysis of monthly meeting minutes and focus group discussions with the implementation team to understand and explain the outcomes of the observational cohort study.Ethics and disseminationThis protocol has been reviewed and approved by the National Health Group Domain Specific Review Board: Reference Number: 2023/00245. Apart from the end-of-study focus group discussions, waiver of informed consent was sought as the data sources were a review of routinely collected retrospective data. The results of this study will be disseminated to peer-reviewed journals, presented at conferences and shared with policy-level stakeholders.